Primbon Jawa sebagai Tradisi Penentuan Hari Nikah: Telaah Konsep Maqashid Al-Syariah - Alma Depa Yanti (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Primbon is a local wisdom that is still often used in determining auspicious days, this tradition is very inherent in Javanese society in marriage, that is, when before the marriage takes place, calculations based on primbon will be carried out for determining the wedding day to avoid any calamities or other disturbances. The purpose of this study is to examine how Javanese people determine their wedding day using Javanese primbon as a tradition that has been used for a long time, using the maqashid al-shariah perspective approach and what are the maslahah and mafsadah in it. This research is a literature study with a normative juridical approach, in which the determination of the wedding day in Javanese primbon is the object of study. This article uses the maqashid al-shariah perspective as the analytical knife, the focus is on the study of determining the day of marriage in Javanese primbon. The results of this study indicate that the determination of the wedding day as a tradition of the Javanese people using the weton calculation when viewed from the perspective of maqasid al-syariah is not contradictory if it is based on Islamic shari'ah, as long as the pillars and conditions of marriage in the tradition are fulfilled, so that the goal will be achieved from maqashid al-shariah, namely maintaining religion (hifz al-Din), soul (hifz al-Nafs), and offspring (hifz al-Nasl).